The perceptions of men awaiting the first child following In vitro fertilization: A qualitative study - Roghieh Bayrami; Fatemeh Effati-Daryani; Masoumeh Hajshafiha; Roksana Janghorban (Tehran University of Medical Sciences, 2018)
Background & Aim: Couples face many problems in pregnancies following In vitro fertilization (IVF) compared to normal pregnancies. The majority of studies have focused on women, and men have received less attention. So, this study aimed to explore the perceptions of men awaiting the first child following IVF. Methods & Materials: This qualitative study was carried out in Shahid Motahari hospital in Urmia during 2017-2018. Data were collected using 19 individual in-depth semi-structured interviews. Participants were selected among men whose wives got pregnant by IVF, through purposeful sampling, until data saturation was reached. Data were analyzed through conventional content analysis approach using the MAXQDA software version 10. Results: Four categories of "hope and fear of treatment outcome", "fear of social stigma", "financial concern", and "need for participation and training" were emerged from data analysis. Conclusion: Men whose wives got pregnant through IVF have expectations and needs that must be addressed. On the one hand, the men are concerned about the social stigma of infertility and donation, the outcome of treatment, and the economic problems of treatment, and on the other hand they expect to be involved in the process of treatment and prenatal care.